2018
DOI: 10.1007/s00270-018-2069-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Short-Term Efficacy of Irreversible Electroporation and Allogenic Natural Killer Cell Immunotherapy Combination in the Treatment of Patients with Unresectable Primary Liver Cancer

Abstract: Our data suggest a novel, promising combination therapy using IRE and allogenic NK cell immunotherapy. Larger clinical trials are required to confirm these conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…130 This initial study, along with a similar investigation for patients with unresectable liver cancer, indicates that IRE could play a ''priming'' role by preparing the tumor microenvironment for effective exploitation by immunotherapy. 137 Further clinical examination has shown that immune modulation occurs quickly after IRE and that attenuation of the highly immunosuppressive environment, as seen by a reduction in regulatory T cells, can be achieved for at least 2 weeks. 138,139 These results are supported by the finding that IRE and anti-PD1 immunotherapy work synergistically to improve survival in a murine model of pancreatic cancer.…”
Section: Immune Modulation and Synergy With Immunotherapymentioning
confidence: 99%
“…130 This initial study, along with a similar investigation for patients with unresectable liver cancer, indicates that IRE could play a ''priming'' role by preparing the tumor microenvironment for effective exploitation by immunotherapy. 137 Further clinical examination has shown that immune modulation occurs quickly after IRE and that attenuation of the highly immunosuppressive environment, as seen by a reduction in regulatory T cells, can be achieved for at least 2 weeks. 138,139 These results are supported by the finding that IRE and anti-PD1 immunotherapy work synergistically to improve survival in a murine model of pancreatic cancer.…”
Section: Immune Modulation and Synergy With Immunotherapymentioning
confidence: 99%
“…In this study including 40 patients, increased OS was observed in the combination therapy group compared with irreversible electroporation monotherapy group (10.1 vs. 8.9 months, p = 0.0078) [86]. In 2019, a similar study conducted in 40 unresectable primary liver cancer patients reported that patients who received combination therapy exhibited superior median PFS and OS compared to those who received irreversible electroporation monotherapy (PFS 15.1 vs. 10.6 months, p < 0.05; OS 17.9 vs. 23.2 months, p < 0.05) [87]. In this study, the allogeneic NK cells were donated by KIR-HLA mismatching relatives and expanded using the in vitro preparation kit (HANK Bioengineering Co., Ltd, Shenzhen, China) [87].…”
Section: Current Nk Cell Therapy In Solid Tumorsmentioning
confidence: 99%
“… 41 Some studies even suggest that immunogenic effect of IRE is more pronounced than in other ablation therapies like radiofrequency ablation 31 and cryoablation. 32 Evidence suggests that administration of immune-stimulating molecules can even enhance the local effectiveness of ECT 35 and IRE 29 , 42 , 43 , 44 allowing simultaneous treatment of distant tumors.…”
Section: Introductionmentioning
confidence: 99%